Characterizing opioid consumption in the 30-day post-operative period following shoulder surgery: are we over prescribing?. Issue 2 (3rd April 2021) - Patel, Manan Sunil; Updegrove, Gary F.; Singh, Arjun M.; Jamgochian, Grant C.; LoBiondo, Deborah; Abboud, Joseph A.; Ramsey, Matthew L.; Lazarus, Mark D.
ABSTRACT: Objectives : The primary aim of this study was to characterize opioid consumption in the first 30 days after shoulder surgery. Secondary aims were to assess patient expectations, pain tolerance, risk factors for increase opioid consumption, and proper disposal of narcotics. Methods : Patients undergoing rotator cuff repair (RCR), anatomic shoulder arthroplasty, reverse shoulder arthroplasty (RSA), distal clavicle resection, or labral surgery were prospectively enrolled. Collected data included demographics, Pain Catastrophizing Scale (PCS), pain tolerance surveys, narcotic use, adverse effects, and disposal method. Results : Eighty patients were included in this study. At 28 days, RCR patients took significantly more 5 mg oxycodone-equivalent pills than RSA patients (18.4 vs. 7.5; p = 0.001). Number of days on narcotics did not differ between groups. By day 14, 73 (92.5%) patients had stopped taking narcotics entirely, with 872 5 mg oxycodone-equivalent pills prescribed in surplus. Ten (14.3%) patients required an additional prescription. There was a significant difference in tobacco use (20% vs. 1.4%; p = 0.04), psychiatric history (50% vs. 5.7%; p = 0.0004) and PCS (12.7 vs. 7.1; p = 0.027) in these patients, with PCS of 12.5 as predictive of requiring another prescription. Conclusion : All patients achieved adequate pain control, with 60 (75%) patients having excess pills. Opioid utilization differed based on surgery – significantly lower use in RSA patients compared to RCR. Only 13 (16.25%) patients required more than 20 5 mg oxycodone-equivalent pills. Tobacco use, history of psychiatric illness, and PCS were risk factors for requiring more prescriptions.